Designing Hydrogels for Controlled Drug Delivery - Cassano, Roberta (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The aim of this book is to provide an analysis of the main characteristics and applications of hydrogels. Hydrogels are frequently used for manufacturing contact lenses, hygiene products, tissue engineering scaffolds, drug delivery systems, and wound dressings. These materials are useful in everyday life, so publicizing them in both academic and pharmaceutical fields is essential.